The architecture of Scotland, 1660-1750 - Humm, Louisa; Lowrey, John; MacKechnie, Aonghus (Edinburgh University Press, 2020)
This architectural survey covers one of Scotland's most important periods of political and architectural change when mainstream European classicism became embedded as the cultural norm. Typologically, the book is broad in scope, covering the architecture and design of country estate and also the urban scene in the era before Edinburgh New Town.